Industrial soft skills seminars - Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
20 March 2012. A three-part series of industrial soft skills seminar are being conducted by the Soft Skills Department of CMLHS for all graduating UMP students. The seminar took a full-stretch of two days for each part.